Harmonizing Social And Religious Values In Sharia Economic Practices - Fachrozi, Fachrozi; Khusnudin, Khusnudin (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This study aims to explore the harmonization of social and religious values within Sharia economic practices, focusing on the Indonesian context. The objective is to understand how these values can be integrated into everyday economic activities to promote ethical behavior and community welfare. Utilizing a systematic literature review (SLR) methodology, the research synthesizes various academic sources to identify key themes, trends, and insights. The thematic analysis reveals that education and awareness are crucial in fostering a Sharia-compliant economic environment. The findings highlight the significant role of Islamic finance in aligning financial practices with social values such as equity and justice, which are essential for community development. Additionally, the research identifies challenges, including diverse religious interpretations and limited awareness, which hinder the growth of Islamic economics in a pluralistic society. The study concludes that targeted educational initiatives and robust regulatory frameworks are necessary to facilitate the acceptance and effectiveness of Sharia economic practices.